Levels of interleukins in patients with chronic kidney disease and periodontitis: a systematic review - Mahmud, Mohemmed; Jesmin, Fabiha; Kassim, Nur Karyatee; Zainuddin, Siti Lailatul Akmar; Hanafi, Muhammad Hafiz; Kamarudin, Muhammad Imran; Ahmad, Farizan; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Wolters Kluwer ‑ Medknow, 2021)
Aim: To systematically review the in vivo clinical studies available in the literature evaluating the effect of interleukin (IL) in patients with chronic kidney disease (CKD) and chronic periodontitis (CP).